Pendampingan Pengembangan Media Pembelajaran Sederhana Berbasis Canva dalam Peningkatan Literasi di SMA Negeri 4 Seram Bagian Timur - Asep, Asep; Loklomin, Samsul Bahri (Jurnal Pengabdian Arumbai, 2024)
The integration of technology in the learning process remains a significant challenge, especially in remote areas like SMA Negeri 4 Seram Bagian Timur. Limited infrastructure and low technological literacy among teachers have led to a lack of innovation in delivering learning materials. This activity aims to improve digital literacy and skills in creating technology-based learning media using Canva. The partner in this activity is SMA Negeri 4 Seram Bagian Timur, targeting 28 students and 1 teacher. The implementation of the activity is carried out in three stages: preparation, implementation, and evaluation. In the preparation stage, materials and tools are prepared. The implementation involves direct training using a Knowledge Transfer approach and the Community Development Model. The training sessions include an introduction to Canva, a workshop on creating media, and mentoring in the design process. Evaluation is done through pre-tests, post-tests, and response questionnaires. The results showed an average post-test score increase to 84.82 from 63.75 in the pre-test. The N-Gain analysis indicated a 57.82% improvement. Recommendations from this activity include the need for ongoing support for infrastructure and advanced technology training so that the skills gained can be consistently applied in the learning process